Effect of poplar ecological retreat project on soil bacterial community structure in Dongting Lake wetland - Wu, Haipeng; Xiao, Sha; Dai, Juan; Xiong, Ying; Cao, Jiao; Qu, Xinyu; Wang, Guiqiao; Yang, Ruiqing (Frontiers in Microbiology, 2022)
As an important environmental protection measure, the Poplar Ecological Retreat (PER) project aims to restore the ecology of the Dongting Lake (DL, China’s second largest freshwater lake) wetland. And its ecological impact is yet to be revealed. The soil bacterial community structure (BCS) is a significant indicator for evaluating soil environment changes. In this study, we investigated the impacts of the PER project on soil BCS in DL wetland. Soil samples from reed area (RA, where poplar had never been planted, as the end point of ecological restoration for comparison in this study), poplar planting area (PA), poplar retreat for 1-year area (PR1A) and poplar retreat for 2 years area (PR2A) were collected. The results showed that the PER project caused the significant changes in soil properties and an increase in diversity and richness index of soil BCS. The Shannon-wiener index of RA, PA, PR1A and PR2A was 3.3, 2.63, 2.75, and 2.87, respectively. The number of operational taxonomic units (OTUs) changed similarly to the Shannon-wiener index. The Pearson correlation analysis and redundancy analysis (RDA) showed that the poplar retreat time, SOM and moisture content were the significant influencing factors. All of these indicated that after the implementation of the PER project, the ecology of the lake area showed a trend of gradual recovery.